2019
DOI: 10.1093/annonc/mdz101.014
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection in breast cancer patients from Mozambique: A prospective cohort study

Abstract: Background: Insight in late treatment-related health problems following from breast cancer treatment is useful in anticipating on the (informational) needs of patients during follow-up. This study aimed to identify treatment-related health problems in breast cancer patients up to five years after diagnosis. Second, use of care associated to these health problems was identified. Methods: 876 surgically treated female patients diagnosed with early stage breast cancer (between 2012-2016) were asked to complete an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Data regarding cancer treatment received by WLWH vs HIV-negative patients were scarce (Supplemental Table 20, http://links.lww.com/QAD/B974). Still, unlike what has been reported in the USA [44], no differences were observed in terms of receipt of surgery, radiotherapy or chemotherapy between WLWH vs HIV-negative women in the Sub-Saharan African studies [6,14,17], but only one of them adjusted survival estimates for treatment [17]. Similarly, no study adjusted survival estimates to CD4+ cell count, antiretroviral therapy or to time since HIV diagnosis.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Data regarding cancer treatment received by WLWH vs HIV-negative patients were scarce (Supplemental Table 20, http://links.lww.com/QAD/B974). Still, unlike what has been reported in the USA [44], no differences were observed in terms of receipt of surgery, radiotherapy or chemotherapy between WLWH vs HIV-negative women in the Sub-Saharan African studies [6,14,17], but only one of them adjusted survival estimates for treatment [17]. Similarly, no study adjusted survival estimates to CD4+ cell count, antiretroviral therapy or to time since HIV diagnosis.…”
Section: Discussionmentioning
confidence: 59%
“…The systematic search of literature provided 10,174 unique citations, of which 62 were reviewed as full text (Figure 1). Among them, 20 publications reporting on 18 studies (including 3,174 WLWH [0.13%] and 2,394,598 HIV-negative women [99.87%]) were included: 15 assessed the likelihood of stage III/IV [6,7,[9][10][11]14,17,[24][25][26][27][28][29][30][31], 10 described each stage at diagnosis [6,7,9,14,17,24,25,27,29,31], nine reported on classic subtypes and ER status [7,9,14,17,25,26,29,31,32], four described surrogate subtypes [17,26,29,31] and seven assessed overall survival [14][15][16][17]27,33,34] -Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In sub-Saharan Africa, estimates of the excess mortality seen among women with HIV (vs HIV-negative women) diagnosed with breast cancer ranged from an increase of 40-50% in South Africa and Mozambique to 80-100% in Botswana and Uganda. [7][8][9][10] Similarly, studies in the USA [11][12][13][14][15] showed an adjusted 50% and 80% increased risk for all-cause and breast cancer-specific mortality, respectively (appendix p 2). A meta-analysis reported a pooled-adjusted 90% increased risk, 16 albeit with marked between-study heterogeneity as most studies were either based on small numbers of women with HIV and, specifically in sub-Saharan Africa, had suboptimal follow-up time or losses to follow-up of greater than 40% (appendix p 2).…”
Section: Introductionmentioning
confidence: 99%